Fenomena Childfree Pada Generasi Milenial Ditinjau Dari Perspektif Islam - Siti Nuroh; M Sulhan (Indonesia, 2022)
This research examines the childfree phenomenon in the millennial generation from an Islamic perspective. The research method used is library research with qualitative descriptive analysis techniques. Childfree is an agreement made by a husband and wife not to have children during their marriage. With the normative approach of the Qur'an and Sunnah, it can be seen that having offspring is a recommendation in Islam, not an obligation. So that childfree is not included in the category of prohibited acts, because every married couple has the right to plan and manage their household life including having children. Nevertheless, even though there is no verse that directly prohibits childfree, as a human being who believes in Allah SWT, the choice to be childfree can be said to be an unwise choice because Allah SWT guarantees the survival of each of his servants. In Islam children are seen as a gift to be grateful for because children are a gift from God. Every human being who is given the mandate to be a parent must carry out this role properly and in totality.